Generalization Strategies in the Problem Solving of Derivative and Integral - Hashemi, Nourooz; Kashefi, Hamidreza; Abu, Mohd Salleh (International Journal on Emerging Mathematics Education, 2019)
This study proposes a learning strategy of derivatives and integrals (LSDI) based on specialized forms of generalization strategies to improve undergraduate students’ problem solving ofderivative and integral. The main goal of this study is to evaluate the effects of LSDI on students’ problem solvingofderivative and integral. The samples of this study were 63 undergraduate students who took Calculus at Islamic Azad University of Gachsaran, Iran. The students were divided into two classes based on their marks in the pre- test of derivative and integral. The results indicated that there was a significant difference between the achievements of students in experimental and control groupsafter treatment. Thus, the findings reveal that using generalization strategies improves students’ achievements in solving problems of derivative and integral.